OPTIMATION STUDY OF CARRAGEENAN EXTRACTION FROM RED ALGAE (Eucheuma cottonii) - Refilda -; Edison Munaf; Rahmiana Zein; Abdi Dharma; Indrawati -; Lee Wah Lim; Toyohide Takeuchi (Jurnal Riset Kimia, 2009)
ABSTRACT Carrageenan is a general name for polysacharides, it is made up of sodium, potassium, magnesium, and calcium sulphat esters of galactose and 3.6-anhydrogalactose units. Research about parameters influencing extraction process of carrageenan from red algae (Eucheuma cottonii) has been studied. The parameters were particle size of red algae, pH of NaOH solution, heating time and heating temperature. About 64.30% of carrageenan was extracted from red algae (Eucheuma cottonii) under optimum condition, 425 µm particle size of red algae, solution pH 8.5, heating time 18 h, and heating temperature 95°C. The FTIR spectra of extracted carrageenan showed the same spectra as the pure carrageenan. Keywords : carrageenan, red algae (Eucheuma cottonii), and extraction